2020
DOI: 10.19111/bulletinofmre.800132
|View full text |Cite
|
Sign up to set email alerts
|

Petrographic characteristics of deep marine turbidite sandstones of the Upper Cretaceous Tanjero Formation, Northwestern Sulaimaniyah, Iraq: implications for provenance and tectonic setting

Abstract: This study was carried out to determine the sedimentary provenance of Upper Cretaceous turbidites of Tanjero Formation. The sandstone portion of the unit has been examined based on field and laboratory studies. Seven sections were measured and described in detail on the perfectly cropped out part of the unit at the southern limb of the Sulaimaniyah Syncline. The thickness of the measured sections varies from 120 m to 192 m. The measured sections start from the top of the underlying Shiranish Formation to the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…The ∼ 240 Ma Triassic age signature in the detrital zircon records of the Amiran and Kashghan formations has been attributed to the mid-oceanic ridge based on the trace element data measured in zircon grains (Barber et al, 2019). Additionally, sandstone petrographic analysis on the Tanjero Formation revealed the occurrence of limestone and chert grains that were particularly sourced from the older Qulqula radiolarite and Balambo formations in the NW (Aziz and Sadiq, 2020;Jones et al, 2020;Çelik and Salih, 2021). Such variation in the sediment source for the proto-Zagros foreland basin is in line with (i) the destruction of the Gotnia Basin architecture, (ii) an input of carbonate material into the new flexural basin, and (iii) the occurrence of some recycled Paleozoic and older zircon grains in the Tanjero Formation (Aqrawi et al, 2010;English et al, 2015;Aziz and Sadiq, 2020;Jones et al, 2020).…”
Section: Detrital Zircon (U-th) / He Thermochronology and (U-th) / He Double-dating Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…The ∼ 240 Ma Triassic age signature in the detrital zircon records of the Amiran and Kashghan formations has been attributed to the mid-oceanic ridge based on the trace element data measured in zircon grains (Barber et al, 2019). Additionally, sandstone petrographic analysis on the Tanjero Formation revealed the occurrence of limestone and chert grains that were particularly sourced from the older Qulqula radiolarite and Balambo formations in the NW (Aziz and Sadiq, 2020;Jones et al, 2020;Çelik and Salih, 2021). Such variation in the sediment source for the proto-Zagros foreland basin is in line with (i) the destruction of the Gotnia Basin architecture, (ii) an input of carbonate material into the new flexural basin, and (iii) the occurrence of some recycled Paleozoic and older zircon grains in the Tanjero Formation (Aqrawi et al, 2010;English et al, 2015;Aziz and Sadiq, 2020;Jones et al, 2020).…”
Section: Detrital Zircon (U-th) / He Thermochronology and (U-th) / He Double-dating Resultsmentioning
confidence: 97%
“…By the Maastrichtian, the proto-Zagros flexural foreland basin started to form in response to the arrival of the Neotethys intraoceanic subduction zone at the Arabian Plate margin, leading to the ophiolite obduction (Stoneley, 1975;Koop and Stoneley, 1982;Alavi, 1994;Homke et al, 2010;Saura et al, 2011;Barber et al, 2019). This process resulted in a basin geometry where the sedimentary infill thinned toward the west with a surge of clastic input sourced mostly from the NW and the NE (Karim and Surdashy, 2005;Aqrawi et al, 2010;Çelik and Salih, 2021). The main clastic formations of the proto-Zagros foreland basin in the Kurdistan region of Iraq are the Tanjero, Kolosh, and Gercus formations with the ages of Maastrichtian, Paleocene, and Eocene, respectively (Fig.…”
Section: The Proto-zagros Foreland Basin Stratamentioning
confidence: 99%
“…Most Cretaceous (Tanjero Formation) sandstones belong to lithic recycled orogen, while Paleogene (Kolosh Formation) sandstones represent transitional recycled orogen. Paleocurrent analysis conducted by Karim and Surdashy (2005b) and Çelik and Salih (2021) of the Tanjero Formation indicate that the source area is located NE of the basin. The area where an uplifted older sedimentary rocks (Fig.…”
Section: Tectonic Setting and Provenancementioning
confidence: 97%
“…However along-strike toward SE, the proto-Zagros strata of the Amiran and Kashghan Formations have a ~240 Ma Triassic age mid-oceanic ridge signature (Zhang et al, 2016;Barber et al, 2019) in addition to the ~100 Ma signature, implying a different paleogeography toward NW. As zircon in mafic rocks is not a common mineral (Grimes et al, 2007), sandstone petrographic analysis on the Tanjero Formation revealed contents of limestone and chert (Aziz and Sadiq, 2020;Jones et al, 2020) that were particularly sourced from the older Qulqula radiolarite and Balambo Formations in 260 the NW (Çelik and Salih, 2021). Such variation in the sediment source for the proto-Zagros foreland basin is in line with the destruction of the Gotnia basin architecture and the recycling of its deposits into the newly flexural basin and the occurrence of some Paleozoic and older zircon grains in the Tanjero Formation (Aqrawi et al, 2010;English et al, 2015;Aziz and Sadiq, 2020;Jones et al, 2020).…”
Section: Provenance Of the Nw Zagros Wedge-top Depositsmentioning
confidence: 99%